2019
DOI: 10.1101/651745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual midbrain and forebrain origins of thalamic inhibitory interneurons

Abstract: 12The proportion and distribution of local inhibitory neurons (interneurons) in the thalamus 13 varies widely across mammals. This is reflected in the structure of thalamic local circuits, 14which is more complex in primates compared to smaller-brained mammals like rodents. 15An increase in the number of thalamic interneurons could arise from addition of novel 16 interneuron types or from elaboration of a plesiomorphic ontogenetic program, common to 17 all mammals. The former has been proposed for the human br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 119 publications
(154 reference statements)
2
10
1
Order By: Relevance
“…Using genetically-encoded Ca 2+ sensors ( Figure 1C, AAV2/5.CaMKII.GCaMP6f) (Chen et al, 2013), we tracked large populations of individual MGB neurons across a four-day auditory fear conditioning paradigm in freely moving mice. Similar to previous reports (Hackett et al, 2016), we found GABAergic fibres, typically originating in inferior colliculus and the thalamic reticular complex (Rouiller et al, 1985;Winer et al, 1996), but virtually no GABAergic somata in MGB ( Figure S1, see also Jager et al, 2019), indicating that we mainly imaged Ca 2+ activity of thalamic relay neurons. We were able to follow 97 ± 5 GCaMP6f-expressing neurons per mouse ( Figures 1D and 1E, N = 19 mice) stably within and across sessions.…”
Section: Resultssupporting
confidence: 90%
“…Using genetically-encoded Ca 2+ sensors ( Figure 1C, AAV2/5.CaMKII.GCaMP6f) (Chen et al, 2013), we tracked large populations of individual MGB neurons across a four-day auditory fear conditioning paradigm in freely moving mice. Similar to previous reports (Hackett et al, 2016), we found GABAergic fibres, typically originating in inferior colliculus and the thalamic reticular complex (Rouiller et al, 1985;Winer et al, 1996), but virtually no GABAergic somata in MGB ( Figure S1, see also Jager et al, 2019), indicating that we mainly imaged Ca 2+ activity of thalamic relay neurons. We were able to follow 97 ± 5 GCaMP6f-expressing neurons per mouse ( Figures 1D and 1E, N = 19 mice) stably within and across sessions.…”
Section: Resultssupporting
confidence: 90%
“…Two integrated types are species-specific and likely represent neurons that were sampled from outside of dLGN, including the mouse GABA1 type (likely representing RTN neurons) and the macaque GABA2 type. The mouse GABAergic types can be roughly divided into two groups based on the expression of key transcriptional regulators (Sox14, Lef1, Otx2, Nkx2-2, and Dlx5) that reflect their developmental origin in the midbrain (Sox14+) or forebrain (Sox14-) (Scholpp and Lumsden, 2010;Jager et al, 2020). All mouse GABAergic types in dLGN and some types in the ventrolateral geniculate nucleus (LGv) and the intergeniculate leaflet (IGL) express Sox14, which is consistent with previous reports (Sellers et al, 2014;Jager et al, 2016).…”
Section: Cross-species Analysis Of Neuronal Cell Types In Dlgnsupporting
confidence: 89%
“…5D ). Two recent studies showed that at least some of the dLGN interneuron developmental programs are conserved between primates and rodents, leading to homology in mature cell types (Golding et al, 2014; Jager et al, 2020). GABAergic neuron diversity in primate dLGN may be increased by an expanded distribution of forebrain-derived, SOX14 -negative neurons that are found predominantly in medial thalamic nuclei in mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transmitter-related bipartition of the prethalamus recalls the subpallio-pallial partition of the neighboring telencephalon, though here no significant mixing of excitatory and inhibitory populations occurs, at least in rodents. The prethalamus also contrasts with its caudal neighbor the thalamus, where mainly glutamatergic cells are produced in rodents, with partial invasion of extrinsic inhibitory interneurons (Jager, Calpin, Durmishi, Shimogori, & Delogu, 2019;Jager et al, 2016;Jeong et al, 2011;S. Martinez & Alvarado-Mallart, 1989).…”
Section: Discussionmentioning
confidence: 99%